Analisis Strategi Promosi dalam Upaya Meningkatkan Kunjungan Wisatawan di Kawasan Wisata Pusuk Sembalun Kabupaten Lombok Utara - Phyta Rahima; Suriyati Suriyati; Isra Dewi Kuntary Ibrahim (Target : Jurnal Manajemen Bisnis, 2023)
Pusuk Sembalun Tourism Park is a natural tourist area that offers a unique view of the slopes of Mount Rinjani, Lombok. The view is dominated by hills, mountains, expanses of rice fields, and traditional houses that have very high historical value. Pusuk Sembalun Tourism Park is located at the foot of Mount Rinjani. The address for the Pusuk Sembalun Tourism Park is on Jl. Jl. Wisata Gunung Rinjani, Sembalun District, East Lombok Regency, West Nusa Tenggara Province (NTB). This study uses the concept of a promotional mix in the form of advertising, personal selling and sales marketing. This study uses a descriptive method using qualitative data. The methods used in collecting data are interviews, observations or coming directly to tourist attractions, and SWOT analysis. The results showed that the form of promotion strategy implemented by Umbul Square Tourism, namely advertising using various TV stations, billboards, and various social media (Instagram, Facebook, YouTube and websites), needs to be implemented in the procurement of waste management according to the category, minimizing use of non-environmentally friendly vehicles. The promotion strategy plays an important role in increasing the number of tourists, the promotional activities carried out by the destination manager are good and need to be improved again so that they are more famous, and tourists want to return to Pusuk Sembalun Tourism